PENGARUH KENYAMANAN FASILITAS WISATA DAN KEPUASAN WISATAWAN TERHADAP KEPUTUSAN WISATAWAN UNTUK BERKUNJUNG KEMBALI KE KAWASAN WISATA GOA RANCANG KENCANA DAN AIR TERJUN SRI GETHUK GUNUNGKIDUL YOGYAKARTA - Kiswantoro, Amin (Kepariwisataan: Jurnal Ilmiah, 2017)
There are significant developments in tourism in Indonesia, indicated by increase in numbers of tourist visit in every popular tourism destination. All destinations now gear up to win the competition in winning tourist interest to visit their facilities. To be able to win the competition, stake holders needs to understand the behavior of the tourist towards their decisions to visit the destinations. The decision to choose which destination to visit is affected by many factors. Two of major factors are satisfaction and facilities. The facilities are includes public facilities, tourist information, dining place, health and safety support facilities, Merchandising and shopping outlets. This research will use quantitative approach by employing samples taken with accidental sampling method from all visitors which happen to be acquainted with the researcher. The data analysis utilizes Multiple Regression Method to determine correlation between multiple independent variables which affecting one dependent variable. The result of the research indicates that simultaneous factor of comfort ability of facilities and the satisfaction affecting the behavior to revisit the destination. However, partially, only the factors of facilities security and visitor’s satisfaction affecting decision to revisit. The other factors were insignificant and not affecting. This research limits it object to The Tourism destination of Goa Rancang Kencana and Sri Gethuk Water Fall at Gunungkidul, Yogyakarta. Keywords: Tourist Facilities, Tourist Satisfaction, Decisions to revisit